A Network Pharmacology Study: Reveal the Mechanisms of Palovarotene Against Heterotopic Ossification - Huang, Junchao; Liu, Dachuan; Zhang, Jingwei; Xiao, Haijun (Frontiers in Medicine, 2022)
Heterotopic ossification (HO) occurs when bone forms within non-ossifying tissues, such as in muscle. Palovarotene, an activator of retinoic acid receptor γ (RAR-γ), has been shown to inhibit the formation of ectopic bone in HO model mice, but its specific mechanism of action remains unclear. This study will explore the target and molecular mechanism of Palovarotene's action on HO by network pharmacology study. We collected the relevant targets of Palovarotene and HO from the database, obtained the potential targets of Palovarotene acting on HO through Venn analysis, and constructed the protein-protein interaction (PPI) network. Then, Gene Ontology (GO) and KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment Analysis and Module-based Network Analysis were performed for potential targets, and in addition, PPI Network Topology Analysis and Gene-Phenotype Correlation Analysis were performed. The results suggested that MAPK1, MDM2 and other targets as well as P53 signaling pathway and PI3K−Akt signaling pathway may be closely related to Palovarotene treatment of HO. We carried out verification experiments to confirm our finding, alkaline phosphatase and alizarin red staining in vitro and Micro-CT as well as hematoxylin-eosin staining in vivo were performed to verify treatment for HO of Palovarotene, reverse transcription polymerase chain reaction was also used to explore the transcription changes of MAPK1, MDM2 and osteogenic genes. This study systematically elucidated the possible mechanism of Palovarotene in the treatment of HO through network pharmacology study, revealing a new direction for the further application of Palovarotene in the treatment of HO.